Telehealthcare for remote monitoring and consultations for people with chronic obstructive pulmonary disease (COPD) - Janjua, Sadia (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effectiveness of remote telehealthcare for monitoring and consultation with a healthcare professional for people with COPD.